Patients' mobility as an indicator for (in)efficiency: A panel data analysis on Italian health care authorities - Elsabetta Mafrolla; Eugenio D'Amico (Health Economics Review, 2013)
This paper investigates the influence of internal managerial patterns of heath care authorities on the decision of patients to migrate towards different health care organizations to avail treatments. The efficiency and productivity issues are analyzed, considering the (passive) migration as a proxy for the (in)efficient service availed. We follow the vote by feet theorization by Tiebout , assuming that citizens can choose to avail a health treatment in a public service provider different from their resident one. The choice for a center that is far from home implies a negative judgment to the alternative health care supplier that is closer to the patient. Testing Fixed Effects Panel Model on a sample of Italian health care authorities, a strong correlation is found among variables in our model and some relevant dependence is tested between patients' mobility behavior and their resident authorities' efficiency in allocating resources on the proper operating cost. Spending in the proper way on health care could bring about an enhancement of performances. Instead, wasting resources is immediately perceived by the patient, who consequently seems to move to a different health care authority.
Keywords: M48; 330; health care management; efficiency in health care; health treatment mobility; operating costs in health care; Fixed Effects Panel Model; Italian health care authorities